Pengaruh Kompetensi Manajerial Kepala Sekolah terhadap Kompetensi Sosial Guru Di SMA Negeri 11 Makassar - Dahlan Dahlan; Hermanu Iriawan; Hamdan Hamdan (Jurnal Ilmiah Ilmu Administrasi Publik, 2017)
The Influence of Managerial Competence Social Competence School Of Teacher In SMA Negeri 11 Makassar. This study aimed to determine the effect of the principal managerial competence of the social competence of teachers at SMAN 11 Makassar. This is a descriptive quantitative research the population of all teachers at SMAN 11 Makassar, which amounted to 74 people. The data analysis technique is descriptive statistical analysis and inferential analysis with data normality test, product moment, and linear regression analysis. The results showed for the level of managerial competence headmaster of SMAN 11 Makassar are in either category, from the aspects of conceptual abilities, human abilities, and engineering capabilities, to the level of social competence of teachers at SMAN 11 Makassar are in either category, from the aspect of adaptation , communication, and interaction, so there is significant influence between the principal managerial competence with social competence of teachers at SMAN 11 Makassar.